Download presentation

Presentation is loading. Please wait.

Published byChastity Taylor Modified over 5 years ago

1
If H is the subgroup in Z 12, then H2 = (a) 5(b) 14 (c) {3, 6, 9, 0} {2}(d) {5, 8, 11, 2} (e) {5, 6, 9, 0}(f) {3, 2, 5}

2
If H is the subgroup in Z 12, then H7 = (a) {3, 6, 9, 0} {7}(b) {3, 7, 10} (c) {7, 10, 1, 4}(d) {7, 2, 9} (e) 10(f) 3 7

3
If H is the subgroup in S 3, then H(1,3) = (a) (1,2,1,3)(b) {(1,3,2), (1,3)} (c) {(1, 3, 2)}(d) {(1, 2, 3)} (e) {(1,2), (1,3)}(f) {(1,2,3), (1, 3)}

4
If H is the subgroup in S 3, then H(1,2) = (a) (1,2,1,2)(b) (2,4) (c) (1,2) 2 (d) {(1, 2)} (e) {(1,2), (2,1)}(f) H

5
If H is the subgroup in Z 4 x Z 6, then H(1,2) = (a) (2,1)(b) (3,4) (c) (2,2) (1,2) (d) {(3,4), (1,0), (3,2), (1,4), (3,0), (1,2)} (e) {(1,2), (2,1), (3,4), (0,5), (1,1), (2,3)} (f) H

6
If H is the subgroup in Z 4 x Z 6, then H(2,0) = (a) (2,1)(b) (3,4) (c) (2,2) (1,2) (d) {(3,4), (1,0), (3,2), (1,4), (3,0), (1,2)} (e) {(1,2), (2,1), (3,4), (0,5), (1,1), (2,0)} (f) H

7
How do we start this proof? (a) Assume A n is a subgroup of S n. (b) (c) Assume a, b H (d) Nonempty:

8
What is the next line of the proof? (a) Assume Ha = Hb (b) Assume ab -1 H (c) Assume a, b H (d) Assume if ab -1 H then Ha = Hb.

9
What is the next line of the proof? (a) Assume Ha = Hb (b) (c) Assume a, b H (d) Assume if ab -1 H then Ha = Hb.

10
What is the next line of the proof? (a) Assume Ha = Hb (b) Assume ab -1 H. (c) Assume a, b H (d) Assume if ab -1 H then Ha = Hb.

11
What is the next line of the proof? (a) Assume Ha = Hb (b) Then a = Hb (c) Then b -1 a H(d) Let y H (e) Let y Ha(f) Let y = ab -1

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google